Performance, digestibility and carcass characteristics of feedlot dairy steers fed diets with different urea levels - Magalhães,K.A. (2006)
The effects of urea levels on feed intake, digestibility and carcass traits of 27 confined cross bred steers weighing 303.25 ± 60.8kg, were evaluated. After weighing, castrating, vaccinating and a period of seven days, three steers were slaughtered at the beginning of the experiment and the remaining 24 were allotted in a completely randomized design to four isonitogenous experimental diets (12% of crude protein) and increasing level of urea on the dry matter-basis (0.0; 0.65; 1.30 and 1.65%) to replace soybean meal, so that the final content of the experimental diets were approximately 22, 37, 50 and 63% of crude protein in the form of NPN. Corn and elephant grass silages were supplied at a 70:30 ratio and the total diet had a 65:35, forage: concentrate ratio on a DM-basis. The urea level did not affect nutrient intake, except for rumen degradable protein (RDP) and total digestible nutrients (TDN) linearly increased in function of diet urea level. The nutrient digestibilities linearly increased except for ether extract and non fiber carbohydrate (NFC). A quadratic effect of diet urea level on daily weight gain and no effect of urea level on carcass traits were observed. Urea can totally replace soybean meal in diets for confined crossed dairy steers allowing gains of 1kg/day. Urea can enhance nutrient digestibility of diets.